Among all these dreamers: essays on dreaming and modern society - Bulkeley, Kelly (SUNY series in dream studies, 1996)
Dreams and social responsibility /Jane White-Lewis --55-year secret /Marion A. Cuddy and Kathryn E. Belicki --Seeking the balance /Herbert W. Schroeder --Reflections on dreamwork with central Alberta Cree /Jayne Gackenbach --Black dreamers in the United States /Anthony Shafton --Sex, gender, and dreams /Carol Schreier Rupprecht --Traversing the living labyrinth /Jeremy Taylor --Invitation at the threshold /Patricia Bulkley --Western dreams about Eastern dreams /Wendy Doniger --Political dreaming /Kelly Bulkeley --Healing crimes /Bette Ehlert --Let's stand up, regain our balance, and look around at the world /Johanna King --Conclusion /Kelly Bulkeley.